Liver transplantation and comprehensive rehabilitation in the reversal of hepatic myelopathy: a case report - Liu, Mingyue; Wang, Rongping; Zhou, Wenwen; Tian, Chunyan; Wang, Qian; Zhang, Qin; Jin, Shasha; Wu, Liang (Frontiers in Medicine, 2024)
Hepatic myelopathy (HM) is a rare complication of end-stage chronic liver disease, primarily presenting as symmetrical lower limb weakness that progresses to spastic paralysis without sensory or sphincter dysfunction. We report a case of decompensated cirrhosis associated with hepatitis B virus and HM. The patient showed significant recovery after liver transplantation (LT) and comprehensive rehabilitation training. We summarize the patient’s clinical characteristics post-diagnosis and the assessment outcomes following integrated treatment.